Determinación de glicemia en pobladores adultos de ambos sexos del sector La Merced, distrito El Porvenir – Trujillo, febrero 2008 - Pashco Morillas, Maritza Janet (2008)
This study we know the results obtained from the determination of blood glucose, made 106 adults belonging to the sector La Merced district of El Porvenir-Trujillo, in february 2008; between the ages of 20 and 60 years. We took blood samples and then they were put to analysis for the enzymatic methods of Glucose Oxidase, so to determinate the concentration of glucose. Of the total number people who participated voluntarily 35% (37) were male and 65% (69) female. The percentage values obtained were distributed as follows: hipoglycemic 6% (6) the latter 50% (3) were male and 50% (3) female; normoglycemic 84%(89) 35% (31) males and 65% (58) females and hiperglycemic 10% (11) ,27% (3) males and 73%(8) females.. According with the biggest percentage of hipoglycemic (33%) were between the ages of 20 - 30 years and 41 – 50 years, on the other hand the biggest percentage of hiperglycemic (55%) were 51 and 60 years old